Long-term monomer elution from bulk-fill composite resins - Dundar, Ayse; Barutcugil, Cagatay; Gul Batmaz, Sevde; Yildirim, Kardelen; Gucluer, Oznur (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the long-term elution of unreacted monomers from bulk-fill composite resins. Material and Methods: Four different restorative bulk-fill composite resins (Filtek Bulk Fill, 3M ESPE; X-tra fil, VOCO; SonicFill, Kerr; and Tetric EvoCeram Bulk Fill, Ivoclar Vivadent) were used. A total of 15 samples per group (5 x 5 x 4 mm) were polymerized with light as a single layer (4 mm). Then the samples were put into 75/25% ethanol/water mixture. Evaluation of monomer release was performed by using High-Performance Liquid Chromatography device. This process was repeated after one hour, 24 hours, and 3 months. One-way analysis of variance was used to determine the differences in monomer release between groups, while the Tukey HSD test was used for multiple comparisons. The paired sample t-test was used to determine the time-dependent changes of the same material. (P  .05).Results: Monomer release was observed in all groups. At the end of 3 months, a statistically significant increase was observed in the amount of almost all monomers released from bulk-fill composites (P 0.05).Conclusion: It can be stated that monomer release still continues from all bulk-fill composite materials after three months.
Keywords: Bulk-fill composite; elution; HPLC; monomer